The synthesis of a novel DDPHC diazonium salt: Investigation of its usability in the determination of phenol and chlorophenols using CV, SWV and DPV techniques - Celik, Haci Hasan; Ozcan, Saniye; Mulazimoglu, Aysen Demir; Yilmaz, Ecir; Mercimek, Bedrettin; Cukurovali, Alaaddin; Mulazimoglu, Ibrahim Ender (Elsevier, 2020)
Electrochemical and spectroelectrochemical properties of newly synthesized diazonium salt of 2-(2-(1,3-dioxo- 3,3a-dihydro-1H-isoindol-2(7aH)-yl)-1-(3 methyl-3-phenylcyclobutyl)ethylidene) hydrazinecarboxamide (DDPHC-DAS) were studied using glassy carbon (GC) electrode. In the current study, surface characterization was performed by cyclic voltammetry (CV). Besides electrochemical impedance spectroscopy (EIS) was used for the electrochemical and spectroelectrochemical characterization. Surface images were obtained using scanning electron microscopy (SEM). After completion of modification and characterization process, DDPHC-DAS surface was examined for the usability for the quantitative determination of phenol and chlorophenol derivatives by using CV, square wave voltammetry (SWV) and differential pulse voltammetry (DPV). Phenol and chlorophenol solutions that were prepared in Britton-Robinson (BR) buffer solution (pH 8-12) were employed in this research. The presented study proves that all of compounds can be quantitatively determined not only simultaneously but also independently.
Keywords: DDPHG-DAS; Cyclic voltammetry; Square wave voltammetry; Differential pulse voltammetry; Chemical sensor electrode